Method for preparing potassium-rich type potassium battery positive electrode material by using chelating agent
By using CMC as a chelating agent and transition metal doping method, a potassium-rich potassium electropositive electrode material was prepared, which solved the problem of poor cycle stability of manganese-based PBAs, and achieved high capacity and long-life potassium ion battery performance.
Patent Information
- Application Number
- CN202510013327.0
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-01-06
- Publication Date
- 2025-04-25
AI Technical Summary
The existing manganese-based Prussian blue analogues (PBAs) cathode materials have limited their application in potassium ion batteries due to their inherent lattice defects, presence of crystallization water and ginger-Taylor effect.
Sodium carboxymethylcellulose (CMC) was used as the chelating agent to prepare potassium-rich potassium-electrode material by co-precipitation at room temperature, combined with transition metal doping to slow down crystal nucleation and growth rate, reduce moisture content and improve crystallinity.
The prepared potassium-rich manganese-based PBAs have a lower moisture content and a high crystallinity, which effectively inhibits the structural deformation during the intercalation and removal of potassium ions, improves the transport efficiency of ions and electrons, reduces the charge transfer resistance, enhances the electrochemical kinetics, and significantly improves the cycling stability.
Smart Images

Figure CN119873860A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of potassium ion battery positive electrode materials, and in particular relates to a method for preparing a potassium-rich potassium battery positive electrode material by using a chelating agent. Background Art
[0002] As energy demand increases, new requirements are also put forward for large-scale energy storage technology. Lithium-ion batteries have been widely used in electrochemical energy storage, but the scarcity and uneven distribution of lithium salt resources limit their further development. Therefore, it is necessary to find alternatives to lithium-ion batteries to supplement or even replace lithium-ion batteries. Potassium ions have similar properties to lithium ions, and the working principle of potassium ion batteries (PIBs) is similar to that of lithium-ion batteries. They are both "rocking chair" batteries. Therefore, based on the abundant resources and low prices of potassium salts themselves, potassium ions have become one of the most promising energy storage devices to replace lithium-ion batteries.
[0003] However, the large size of potassium ions makes it a huge challenge to find suitable cathode materials for the development of potassium ion batteries. Currently, the cathode materials that can be used in potassium ion batteries can be roughly divided into layered metal oxides, polyanionic compounds, organic compounds and Prussian blue analogs. Among them, Prussian blue analogs (PBAs) have attracted widespread attention due to their 3D large framework structure that can accommodate large potassium ion insertion and extraction, high capacity, suitable working potential, low cost, and good thermal stability.
[0004] Among the various PBAs, manganese-based PBAs are attractive cathode materials due to their non-toxicity, low cost and high energy density. However, like other transition metal ion-based PBAs, the inherent [Fe(CN)6] 4- The presence of lattice defects and crystal water seriously affects the electrochemical performance of the battery, limiting its further development in the field of energy storage. At the same time, the Jan-Taylor effect of manganese-based materials also leads to structural deformation during the cycle and reduces the cycle stability of the battery. Therefore, reducing the internal defects of PBAs, improving crystallinity, reducing water molecules, and alleviating the Jan-Taylor deformation during the cycle are crucial to improving the cycle stability of manganese-based PBAs. How to solve the above series of problems to meet the requirements of potassium ion batteries with high capacity and long cycle life has become a technical problem that needs to be solved urgently. Summary of the invention
[0005] To solve the problems of the existing technology, the purpose of the present invention is to provide a method for preparing potassium-rich manganese-based Prussian blue analogues (PBAs) as the cathode material for potassium batteries using CMC as a chelating agent. The potassium-rich cathode material for potassium batteries prepared by the present invention has a low water content (far lower than the crystallization water of more than 10% without a chelating agent) and a high crystallinity, which can improve the performance of potassium-ion batteries. The synergistic effect between the doped transition metal elements effectively inhibits the deformation of the PBAs structure during the insertion and extraction of potassium ions. The combined action of the two promotes ion and electron transport and effectively reduces the problems of Mn 2+ dissolution and water-related side reactions, thereby reducing the charge transfer resistance and enhancing the electrochemical kinetics.
[0006] The present invention adopts the following technical solutions.
[0007] The present invention provides a method for preparing a potassium-rich cathode material for potassium batteries using a chelating agent. The potassium-rich cathode material for potassium batteries is potassium-rich manganese-based Prussian blue analogue K x Tm y Mn 1-y (Fe(CN)6, where 0 < x ≤ 2, 0 < y < 1, which is prepared by the room-temperature co-precipitation method; it includes the following steps: a) Mix deionized water, concentrated hydrochloric acid, potassium chloride and a chelating agent to obtain a first solution, which is divided into two parts for standby; among them: the chelating agent is sodium carboxymethyl cellulose CMC; b) Add potassium ferrocyanide to one part of the first solution to obtain a second solution; c) Add a transition metal salt to the other part of the first solution to obtain a third solution; d) Add the second solution to the third solution, stir and age; e) Centrifuge and collect the product obtained in step d), then wash and dry it to obtain a cathode material with high crystallinity and low crystallization water.
[0008] In the present invention, in step a), the volume of the concentrated hydrochloric acid is 0 - 8.62 mL, the mass of potassium chloride is 7.45 - 37.25 g, and the mass of the chelating agent is 30 - 500 mg; among them: the main role of potassium chloride is to ensure potassium richness, and the main role of hydrochloric acid is to provide an acidic environment to trigger the co-precipitation reaction; the role of the chelating agent is to slowly release metal ions and slow down the reaction rate to improve crystallinity.
[0009] In the present invention, in step a), the volume of the concentrated hydrochloric acid is 0 - 2 mL, the mass of potassium chloride is 10 - 25 g, and the mass of the chelating agent is 50 - 200 mg.
[0010] In the present invention, in step b), the potassium ferrocyanide is trihydrate, and the mass is 0.211 - 21.1 g.
[0011] In the present invention, in step b), the mass of potassium ferrocyanide trihydrate is 0.5-5g.
[0012] In the present invention, in step c), the transition metal salt is one or more of Fe, Mn, Ni, Co, and Cu salts, and the molar ratio of the total amount of transition metal atoms in the first transition metal salt and the second transition metal salt to potassium ferrocyanide is 0.1:1 to 1:1.
[0013] In the present invention, in step c), the first transition metal salt is a divalent Mn salt, the second transition metal salt is selected from any one of a divalent Fe salt, a divalent Ni salt, a divalent Co salt or a divalent Cu salt, and the molar ratio of the total amount of transition metal atoms in the first transition metal salt and the second transition metal to potassium ferrocyanide is 1:1.
[0014] In the present invention, in step d), the rate of adding the second solution to the third solution is 0.1-1 mL·min -1 The transition metal salt is added with potassium ferrocyanide. Under the premise of ensuring an excess of potassium ferrocyanide, the transition metal salt slowly replaces potassium ions and co-precipitates. The stirring time is 1 to 3 hours, and the aging time is 4 to 7 hours.
[0015] In the present invention, in step e), washing is performed with ethanol and water; the drying temperature is 80-110° C., and the drying time is 8-24 hours.
[0016] The present invention also provides a potassium-rich potassium positive electrode material prepared by the above method.
[0017] Furthermore, the present invention provides a potassium ion battery, comprising a positive electrode, a negative electrode, a separator and an electrolyte, wherein the positive electrode is made of the above-mentioned potassium-rich potassium-ion positive electrode material.
[0018] Compared with the prior art, the present invention has the following obvious outstanding substantive features and significant advantages: 1. The present invention adopts a simple room temperature coprecipitation method, uses a lower cost CMC chelating agent and combines transition metal doping to slow down the rate of crystal nucleation and growth, so that the prepared Prussian blue analogue has a lower water content and a higher crystallinity, and synthesizes high-quality potassium-manganese-rich PBAs with good cyclic stability.
[0019] 2. The present invention uses the synergistic effect between the doped transition metal elements to effectively inhibit the deformation of the Prussian blue analog structure during the insertion and extraction of potassium ions. The synergistic effect with the CMC chelating agent promotes the transport of ions and electrons, effectively reducing the Mn 2+ The problem of dissolution and water-related side reactions is solved, thereby reducing the charge transfer resistance and enhancing the electrochemical kinetics.
[0020] 3. The electrode material prepared by the present invention was tested. The results showed that the potassium ion positive electrode prepared by the present invention has a conductivity of 60 mA g -1 The specific capacity can still reach 99.1 mAh g after 450 cycles at a current density of -1 , retention rate is 80%; 300 mA g -1 The capacity of the high current density cycle almost stops decaying after 500 cycles, showing good cycle stability. The preparation method of the present invention is simple, the process cost is low, and it is suitable for large-scale production. BRIEF DESCRIPTION OF THE DRAWINGS
[0021] In order to more clearly illustrate the embodiments of the present invention or the technical solutions in the prior art, the drawings required for use in the embodiments or the description of the prior art will be briefly introduced below. Of course, the drawings in the following description are only embodiments of the present invention. For ordinary technicians in this field, other drawings can be obtained based on the provided drawings without paying creative work.
[0022] Figure 1 This is the XRD diffraction pattern of the positive electrode material prepared in Example 1 of the present invention.
[0023] Figure 2 This is a thermogravimetric (TGA) analysis comparison chart of the positive electrode material prepared in Example 1 of the present invention, a potassium-rich manganese-based Prussian blue analog sample synthesized using potassium citrate as a chelating agent and a sample without a chelating agent.
[0024] Figure 3 The morphology and structure diagram of the positive electrode material prepared in Example 1 of the present invention include (a) SEM; (b) TEM; (c) HRTEM and (di) EDS element surface distribution diagram.
[0025] Figure 4 (a) Full XPS spectrum of the cathode material prepared in Example 1 of the present invention; (b) High-resolution XPS spectra of Mn 2p and (c) Fe 2p.
[0026] Figure 5 The potassium-rich manganese-based Prussian blue analogue samples prepared in Example 1 of the present invention using potassium citrate as a chelating agent and the samples prepared without a chelating agent as positive electrode materials for potassium ion batteries have a current density of 60 mA g in a half-cell. -1 The charge-discharge cycle stability curve.
[0027] Figure 6 This is the rate performance of the positive electrode material prepared in Example 1 of the present invention.
[0028] Figure 7 The positive electrode material prepared in Example 1 of the present invention has a current density of 300 mA g in the half-cell.-1 Charge and discharge cycle stability curve at high current.
[0029] Figure 8 This is the thermogravimetric test of the product HS-PBAs obtained in Example 11.
[0030] FIG9 shows the product HS-PBAs obtained in Example 11 and Mn-PBAs synthesized with only Mn element under the same conditions at a current density of 60 mA g -1 The cycle performance diagram below. DETAILED DESCRIPTION
[0031] The positive electrode material prepared by the preparation technology adopted in the following embodiments of the present invention uses CMC chelating agent combined with transition metal doping to slow down the rate of crystal nucleation and growth, so that the prepared potassium-manganese-rich PBAs have lower water content and higher crystallinity.
[0032] The following examples of the present invention adopt a simple room temperature coprecipitation method and a lower cost CMC chelating agent to prepare potassium-manganese-rich PBAs with higher crystallinity and lower water content. The method has a simple preparation method, low process cost, and is suitable for large-scale production.
[0033] The following embodiments of the present invention have no special restrictions on the types of electrodes, separators and electrolytes. The electrodes are potassium sheets; the separators can be glass fiber separators; and the electrolyte is a mixture of ethylene carbonate (EC) and diethyl carbonate (DEC). Specifically, the following embodiments of the present invention simply slice the positive electrode material directly into a positive electrode; the negative electrode is a potassium sheet, a two-component mixed solvent of 1 M KPF6 EC:DEC=1:1 is used as the electrolyte, and a Whatman glass fiber separator is used as the separator, and a CR2016 simulated battery is assembled.
[0034] The following examples of the present invention use 60 mA g -1 The constant current charge and discharge experiment was carried out to test the cycle performance of the potassium ion battery, and the charge and discharge voltage was limited to 3-4.3 V. The CT2001A battery test system of Wuhan Blue Electric Electronics Co., Ltd. was used to test the electrochemical performance of the battery at room temperature. The results show that the potassium ion battery in the following embodiment of the present invention is 60 mA g -1 Charge and discharge at current density, 60 mA g -1 The specific capacity can still reach 99.1 mAh g after 450 cycles at a current density of -1 , with good cycle stability and high capacity.
[0035] In order to further illustrate the present invention, the following is a detailed description of a method for synthesizing potassium-rich manganese-based PBAs as a potassium-rich potassium cathode material using CMC as a chelating agent provided by the present invention, and the performance of a high-capacity, long-life potassium ion battery in combination with embodiments, but it should not be construed as limiting the scope of protection of the present invention.
[0036] The above scheme is further described below in conjunction with specific implementation examples. The preferred embodiments of the present invention are described in detail as follows.
[0037] Example 1
[0038] In this embodiment, a method for preparing potassium-rich manganese-based PBAs as potassium-rich potassium cathode materials using CMC as a chelating agent comprises the following steps: a). Dissolve 100 mg CMC in 100 mL deionized water, add 11.92 g KCl, stir for 12 h, and divide the solution into two parts for later use.
[0039] b). Add 0.4 mmol FeSO4·7H2O and 1.6 mmol MnSO4·H2O into 50 mL CMC solvent and record it as solution A. Add 2 mmol K4Fe(CN)6 into 50 mL CMC solvent and record it as solution B, and stir them for 1 h respectively.
[0040] c). The stirred solution A was slowly dripped into solution B under N2 atmosphere and kept stirring for 2 h. After aging for 6 h, the sample was collected by centrifugation, washed three times with deionized water and ethanol respectively, and then placed in a vacuum drying oven and dried at 100°C for 12 h to obtain the potassium-manganese-based Prussian blue analog FeMn-PBAs-CMC.
[0041] Example 2
[0042] In this embodiment, a method for preparing potassium-rich manganese-based PBAs as potassium-rich potassium cathode materials using CMC as a chelating agent comprises the following steps: a). Dissolve 100 mg CMC in 100 mL deionized water, add 11.92 g KCl and 0.43 mL 36% concentrated hydrochloric acid, stir for 12 h, and divide the solution into two portions for later use as solvent.
[0043] b). Add 0.4 mmol FeSO4·7H2O and 1.6 mmol MnSO4·H2O into 50 mL CMC solvent and record it as solution A. Add 2 mmol K4Fe(CN)6 into 50 mL CMC solvent and record it as solution B, and stir them for 1 h respectively.
[0044] c). The stirred solution A was slowly dripped into solution B under N2 atmosphere and kept stirring for 2 h. After aging for 6 h, the sample was collected by centrifugation, washed three times with deionized water and ethanol respectively, and then placed in a vacuum drying oven and dried at 100 °C for 12 h to obtain a potassium-manganese-rich Prussian blue analog.
[0045] Example 3
[0046] In this embodiment, a method for preparing potassium-rich manganese-based PBAs as potassium-rich potassium cathode materials using CMC as a chelating agent comprises the following steps: a). Dissolve 100 mg CMC in 100 mL deionized water, add 14.9 g KCl, stir for 12 h, and divide the solution into two portions for later use as solvent.
[0047] b). Add 0.4 mmol FeSO4·7H2O and 1.6 mmol MnSO4·H2O into 50 mL CMC solvent and record it as solution A. Add 2 mmol K4Fe(CN)6 into 50 mL CMC solvent and record it as solution B, and stir them for 1 h respectively.
[0048] c). The stirred solution A was slowly dripped into solution B under N2 atmosphere and kept stirring for 2 h. After aging for 6 h, the sample was collected by centrifugation, washed three times with deionized water and ethanol respectively, and then placed in a vacuum drying oven and dried at 100 °C for 12 h to obtain a potassium-manganese-rich Prussian blue analog.
[0049] Example 4
[0050] In this embodiment, a method for preparing potassium-rich manganese-based PBAs as potassium-rich potassium cathode materials using CMC as a chelating agent comprises the following steps: a). Dissolve 120 mg CMC in 100 mL deionized water, add 11.92 g KCl, stir for 12 h, and divide the solution into two portions for later use as solvent.
[0051] b). Add 0.4 mmol FeSO4·7H2O and 1.6 mmol MnSO4·H2O into 50 mL CMC solvent and record it as solution A. Add 2 mmol K4Fe(CN)6 into 50 mL CMC solvent and record it as solution B, and stir them for 1 h respectively.
[0052] c). The stirred solution A was slowly dripped into solution B under N2 atmosphere and kept stirring for 2 h. After aging for 6 h, the sample was collected by centrifugation, washed three times with deionized water and ethanol respectively, and then placed in a vacuum drying oven and dried at 100 °C for 12 h to obtain a potassium-manganese-rich Prussian blue analog.
[0053] Example 5
[0054] In this embodiment, a method for preparing potassium-rich manganese-based PBAs as potassium-rich potassium cathode materials using CMC as a chelating agent comprises the following steps: a). Dissolve 120 mg CMC in 100 mL deionized water, add 14.9 g KCl and stir for 12 h. Divide the solution into two portions for later use.
[0055] b). Add 0.4 mmol FeSO4·7H2O and 1.6 mmol MnSO4·H2O into 50 mL CMC solvent and record it as solution A. Add 2 mmol K4Fe(CN)6 into 50 mL CMC solvent and record it as solution B, and stir them for 1 h respectively.
[0056] c). The stirred solution A was slowly dripped into solution B under N2 atmosphere and kept stirring for 2 h. After aging for 6 h, the sample was collected by centrifugation, washed three times with deionized water and ethanol respectively, and then placed in a vacuum drying oven and dried at 100 °C for 12 h to obtain a potassium-manganese-rich Prussian blue analog.
[0057] Example 6
[0058] In this embodiment, a method for preparing potassium-rich manganese-based PBAs as potassium-rich potassium cathode materials using CMC as a chelating agent comprises the following steps: a). Dissolve 120 mg CMC in 100 mL deionized water, add 14.9 g KCl and 0.43 mL 36% concentrated hydrochloric acid, stir for 12 h, and divide the solution into two portions for later use as solvent.
[0059] b). Add 0.4 mmol FeSO4·7H2O and 1.6 mmol MnSO4·H2O into 50 mL CMC solvent and record it as solution A. Add 2 mmol K4Fe(CN)6 into 50 mL CMC solvent and record it as solution B, and stir them for 1 h respectively.
[0060] c). The stirred solution A was slowly dripped into solution B under N2 atmosphere and kept stirring for 2 h. After aging for 6 h, the sample was collected by centrifugation, washed three times with deionized water and ethanol respectively, and then placed in a vacuum drying oven and dried at 100 °C for 12 h to obtain a potassium-manganese-rich Prussian blue analog.
[0061] Example 7
[0062] In this embodiment, a method for preparing potassium-rich manganese-based PBAs as potassium-rich potassium cathode materials using CMC as a chelating agent comprises the following steps: a). Dissolve 160 mg CMC in 100 mL deionized water, add 14.9 g KCl and 0.43 mL 36% concentrated hydrochloric acid, stir for 12 h, and divide the solution into two portions for later use as solvent.
[0063] b). Add 0.4 mmol FeSO4·7H2O and 1.6 mmol MnSO4·H2O into 50 mL CMC solvent and record it as solution A. Add 2 mmol K4Fe(CN)6 into 50 mL CMC solvent and record it as solution B, and stir them for 1 h respectively.
[0064] c). The stirred solution A was slowly dripped into solution B under N2 atmosphere and kept stirring for 2 h. After aging for 6 h, the sample was collected by centrifugation, washed three times with deionized water and ethanol respectively, and then placed in a vacuum drying oven and dried at 100 °C for 12 h to obtain a potassium-manganese-rich Prussian blue analog.
[0065] Example 8
[0066] In this embodiment, a method for preparing potassium-rich manganese-based PBAs as potassium-rich potassium cathode materials using CMC as a chelating agent comprises the following steps: a). Dissolve 100 mg CMC in 100 mL deionized water, add 14.9 g KCl and 0.43 mL 36% concentrated hydrochloric acid, stir for 12 h, and divide the solution into two portions for later use as solvent.
[0067] b). Add 0.6 mmol FeSO4·7H2O and 2.4 mmol MnSO4·H2O into 50 mL CMC solvent and record it as solution A. Add 3 mmol K4Fe(CN)6 into 50 mL CMC solvent and record it as solution B, and stir them for 1 h respectively.
[0068] c). The stirred solution A was slowly dripped into solution B under N2 atmosphere and kept stirring for 2 h. After aging for 6 h, the sample was collected by centrifugation, washed three times with deionized water and ethanol respectively, and then placed in a vacuum drying oven and dried at 100 °C for 12 h to obtain a potassium-manganese-rich Prussian blue analog.
[0069] Example 9
[0070] In this embodiment, a method for preparing potassium-rich manganese-based PBAs as potassium-rich potassium cathode materials using CMC as a chelating agent comprises the following steps: a). Dissolve 150 mg CMC in 100 mL deionized water, add 14.9 g KCl, stir for 12 h, and divide the solution into two portions for later use as solvent.
[0071] b). Add 0.2 mmol FeSO4·7H2O and 0.8 mmol MnSO4·H2O into 50 mL CMC solvent and record it as solution A. Add 1 mmol K4Fe(CN)6 into 50 mL CMC solvent and record it as solution B, and stir them for 1 h respectively.
[0072] c). The stirred solution A was slowly dripped into solution B under N2 atmosphere and kept stirring for 2 h. After aging for 6 h, the sample was collected by centrifugation, washed three times with deionized water and ethanol respectively, and then placed in a vacuum drying oven and dried at 100 °C for 12 h to obtain a potassium-manganese-rich Prussian blue analog.
[0073] Example 10
[0074] In this embodiment, a method for preparing potassium-rich manganese-based PBAs as potassium-rich potassium cathode materials using CMC as a chelating agent comprises the following steps: a). Dissolve 100 mg CMC in 100 mL deionized water, add 22.35 g KCl, stir for 12 h, and divide the solution into two portions for later use.
[0075] b). Add 0.4 mmol FeSO4·7H2O and 1.6 mmol MnSO4·H2O into 50 mL CMC solvent and record it as solution A. Add 2 mmol K4Fe(CN)6 into 50 mL CMC solvent and record it as solution B, and stir them for 1 h respectively.
[0076] c). The stirred solution A was slowly dripped into solution B under N2 atmosphere and kept stirring for 2 h. After aging for 6 h, the sample was collected by centrifugation, washed three times with deionized water and ethanol respectively, and then placed in a vacuum drying oven and dried at 100 °C for 12 h to obtain a potassium-manganese-rich Prussian blue analog.
[0077] Embodiment 11
[0078] In this embodiment, a method for preparing potassium-rich manganese-based PBAs as potassium-rich potassium cathode materials using CMC as a chelating agent comprises the following steps: a). Dissolve 100 mg CMC in 100 mL deionized water, add 7.45 g KCl, stir for 12 h, and divide the solution into two parts for later use as solvent.
[0079] b). Add 0.4 mmol FeSO4· 7H2O, 0.4 mmol Co(NO3)2·6H2O, 0.4 mmol NiCl2·6H2O, 0.4 mmol MnSO4·H2O, and 0.4 mmol CuSO4·5H2O into 50 mL CMC solvent and record it as solution A. Add 2 mmol K4Fe(CN)6 into 50 mL CMC solvent and record it as solution B, and stir them for 1 h respectively.
[0080] c). The stirred solution A was slowly dripped into solution B under N2 atmosphere and kept stirring for 2 h. After aging for 6 h, the sample was collected by centrifugation, washed three times with deionized water and ethanol respectively, and then placed in a vacuum drying oven and dried at 100°C for 12 h to obtain potassium-manganese-based Prussian blue analogues HS-PBAs.
[0081] Figure 1 This is the XRD diffraction pattern of the PBAs prepared in Example 1, which shows that the diffraction peaks at 2θ=17.56°, 24.8°, 35.48°, 39.71°, and 43.95° correspond to the (002), (111), (004), (220), and (202) crystal planes, respectively. The sharp peaks indicate that the material has good crystallinity and no stray peaks are generated, corresponding to PDF#51-1896.
[0082] Figure 2Thermogravimetric (TGA) analysis comparison chart of the potassium-rich manganese-based Prussian blue analogue samples synthesized by PBAs (FeMn-PBAs-CMC) prepared in Example 1, potassium citrate as a chelating agent (FeMn-PBAs-CIT) and no chelating agent (FeMn-PBAs). According to the results of TGA, it can be found that the early weight loss can be divided into two stages, the first stage is the weight loss of adsorbed water, and the second stage is the weight loss of crystallized water. As shown in the figure, the crystallization water content in the FeMn-PBAs-CMC sample is much lower than that of the FeMn-PBAs-CIT (5.34%) and FeMn-PBAs samples (12.95%), only 0.38%.
[0083] Figure 3 This is a morphology structure diagram of the product obtained in Example 1. Figure 3 (a) Figure 3 As shown in (b), it can be seen that the morphology of the sample is nanoparticles and the particle size is relatively uniform. Figure 3 (c) is the HRTEM image of the sample, in which clear lattice fringes can be seen, and the lattice spacing is 0.505 nm, corresponding to the (002) crystal plane of the sample, which is consistent with the XRD result. The element distribution of the sample was observed by EDS, such as Figure 3 As shown in (di), the Fe, Mn, K, C and N elements in the material are evenly distributed. In summary, the potassium-manganese-rich Prussian blue analog particle sample was successfully synthesized by a simple co-precipitation method.
[0084] Figure 4 The full XPS spectrum of the product obtained in Example 1 and the high-resolution XPS spectrum of Mn 2p and Fe 2p are shown in Figure 4 (a). The characteristic peaks of K 1s, Mn 2p, Fe 2p, O 1s, N 1s and C 1s are observed in the full XPS spectrum of the obtained sample. The presence of the O 1s characteristic peak is caused by the crystal water and adsorbed water inside the unit cell. Figure 4 (b) is the high-resolution XPS spectrum of Mn 2p. In the figure, peaks at binding energies of 652.8 and 640.6 eV can be observed, belonging to Mn 2p 3 / 2 and Mn 2p 1 / 2 In addition, a satellite peak at 646.4 eV can be observed. This indicates that Mn 2+ existence. Figure 4 The high-resolution XPS spectrum of Fe 2p in (c) shows two peaks at binding energies of 707.8 and 720.6 eV, which belong to Fe 2p and Fe 2p respectively. 3 / 2 and Fe 2p 1 / 2, indicating that the initial valence state of the Fe element is + 2. XPS analysis of the valence state of the element confirmed that the FeMn-PBAs-CMC sample has dual redox sites and can provide a higher specific capacity.
[0085] Figure 5 The product FeMn-PBAs-CMC obtained in Example 1, as well as potassium citrate as a chelating agent (FeMn-PBAs-CIT) and no chelating agent (FeMn-PBAs) were used to synthesize PBAs as positive electrode materials for potassium ion batteries at 60 mA g -1 The cycling stability of FeMn-PBAs-CMC shows that it has a long cycle life of more than 450 cycles, and the specific capacity can still reach 99.1 mAh g after 450 cycles. -1 The retention rate is 80%, which shows good cycle stability. Although the FeMn-PBAs-CIT electrode has 92.4 mAh g -1 The first cycle discharge capacity of FeMn-PBAs is high, but it decays rapidly during the cycling process. The Coulombic efficiency (CE) of FeMn-PBAs electrodes is always low during the cycling process.
[0086] Figure 6 The rate performance of the product FeMn-PBAs-CMC obtained in Example 1 is shown in Figure 1 at current densities of 60, 90, 120, 150, 300, and 450 mA g -1 When the discharge capacity of FeMn-PBAs-CMC samples is 124.7, 102.9, 94.5, 87.8, 64.9, and 46.1 mAh g -1 It is worth noting that when the current density increases from 450 mA g -1 Gradually recover to 30 mA g -1 After that, the discharge capacity of the FeMn-PBAs-CMC sample can not only be restored to the original level (124.0 mA g -1 ), while continuing to cycle stably, which further proves that the structure of the PBAs-CMC electrode can remain stable after high-current charge-discharge cycles.
[0087] Figure 7 The product obtained in Example 1 was -1 The high current cycling stability is shown in the figure. It has a long cycle life of 1500 cycles, and the capacity of the electrode hardly decays after 500 cycles, showing good cycling stability.
[0088] Figure 8This is the thermogravimetric test of the product HS-PBAs obtained in Example 11. The curve is divided into three parts. The first part is around 0-70°C, and the slope of the curve is relatively large, indicating the loss of adsorbed water and interstitial water in the early heating process (2.63%). The second part is 70-300°C, and the curve slowly decreases, corresponding to the loss of crystallized water (2.12%). Finally, the curve gradually flattens, indicating that all the water in the material is lost and the material itself begins to decompose.
[0089] FIG9 shows the product HS-PBAs obtained in Example 11 and Mn-PBAs synthesized with only Mn element under the same conditions at a current density of 60 mA g -1 The initial charge capacity and discharge capacity of the HS-PBAs electrode are 125.8 mAh g -1 and 107.6 mAh g -1 The initial Coulombic efficiency (ICE) is 85.49%. The initial charge capacity and discharge capacity of the Mn-PBAs electrode are 178.3 mAh g -1 and 85.9 mAh g -1 , ICE is much lower than that of HS-PBAs electrode (48.19%), which means that there is a large amount of K + The formation of solid electrolyte interface (SEI) and other irreversible reactions lead to capacity loss. After 700 cycles, the HS-PBAs electrode still has 90.6 mAh g -1 The discharge capacity of the Mn-PBAs electrode at the same current density was 85.9 mAh g -1 The discharge capacity of the battery is very high, but it experiences rapid capacity decay, and the discharge capacity can only be maintained at 39.2% after 100 cycles.
[0090] The above embodiment of the present invention provides a method for synthesizing a high-quality material with good cycle stability, potassium-rich manganese-based PBAs, namely K, by using a simple room temperature coprecipitation method, a lower-cost CMC chelating agent and a Fe doping method. x Tm y Mn 1-y(Fe(CN)6) method and application of high-capacity and long-life potassium ion battery performance. First, a certain proportion of hydrochloric acid, potassium chloride and CMC are added to deionized water as solvents, and a certain proportion of potassium ferrocyanide and a certain proportion of transition metal salt are added to each of the two parts. The two solutions are slowly mixed together, stirred, aged, centrifuged, collected, and dried to obtain a positive electrode material for a potassium ion battery. The present invention adopts a low-cost CMC chelating agent and combines it with a transition metal doping method to slow down the rate of crystal nucleation and growth, so that the prepared potassium-manganese-rich PBAs have a lower water content and a higher degree of crystallinity, and the synergistic effect between the doped transition metal elements is used to effectively inhibit the deformation of PBAs during the insertion and removal of potassium ions. The combined effect of the two promotes the transport of ions and electrons, effectively reducing the Mn 2+ The problem of dissolution and water-related side reactions is solved, thereby reducing the charge transfer resistance and enhancing the electrochemical kinetics. The potassium ion battery assembled with PBAs electrodes in the present invention has a high conductivity at 60 mA g -1 The specific capacity can still reach 99.1 mAh g after 450 cycles at a current density of -1 , retention rate is 80%; 300 mA g -1 The capacity of the high current density cycle is almost no longer decayed after 500 cycles, and has excellent cycle stability. The preparation method of the above embodiment of the present invention is simple, the process cost is low, and it is suitable for large-scale production.
[0091] The embodiments of the present invention are described above in conjunction with the accompanying drawings, but the present invention is not limited to the above embodiments. Various changes can be made according to the purpose of the invention of the present invention. Any changes, modifications, substitutions, combinations or simplifications made according to the spirit and principle of the technical solution of the present invention should be equivalent replacement methods. As long as they meet the purpose of the invention of the present invention and do not deviate from the technical principles and inventive concepts of the present invention, they belong to the protection scope of the present invention.
Claims
1. A method for preparing a potassium-rich potassium cathode material using a chelating agent, characterized in that: The potassium-rich potassium-ion battery cathode material is potassium-rich manganese-based Prussian blue analogue K x Tm y Mn 1-y Fe(CN)6, where 0 < x ≤ 2, 0 < y < 1, and it is prepared by the room-temperature coprecipitation method; the method includes the following steps: a) mixing deionized water, concentrated hydrochloric acid, potassium chloride and a chelating agent to obtain a first solution, and dividing the solution into two parts for standby use; wherein the chelating agent is sodium carboxymethyl cellulose CMC; b) adding potassium ferrocyanide to a portion of the first solution to obtain a second solution; c) adding a first transition metal salt and a second transition metal salt to another portion of the first solution to obtain a third solution; the first transition metal salt is a Mn salt, and the second transition metal salt is selected from one or more of Fe, Ni, Co, and Cu salts; d) adding the third solution to the second solution, stirring and aging; e) collecting the product obtained in step d) by centrifugation, washing and drying, and obtaining a positive electrode material with high crystallinity and low crystal water.
2. The method according to claim 1, characterized in that In step a), the volume of concentrated hydrochloric acid is 0-8.62 mL, the mass of potassium chloride is 7.45-37.25 g, and the mass of the chelating agent is 30-500 mg.
3. The method according to claim 1, characterized in that In step a), the volume of concentrated hydrochloric acid is 0-2 mL, the mass of potassium chloride is 10-25 g, and the mass of the chelating agent is 50-200 mg.
4. The method according to claim 1, characterized in that In step b), the potassium ferrocyanide is trihydrate with a mass of 0.211-21.1 g.
5. The method according to claim 4, characterized in that In step b), the mass of potassium ferrocyanide trihydrate is 0.5-5 g.
6. The method according to claim 1, characterized in that In step c), the molar ratio of the transition metal atoms in the first transition metal salt and the second transition metal salt to potassium ferrocyanide is 0.1:1 to 1:
1.
7. The method according to claim 6, characterized in that In step c), the first transition metal salt is a divalent Mn salt, the second transition metal salt is selected from any one of a divalent Fe salt, a divalent Ni salt, a divalent Co salt or a divalent Cu salt, and the molar ratio of the total amount of transition metal atoms in the first transition metal salt and the second transition metal to potassium ferrocyanide is 1:
1.
8. The method according to claim 1, characterized in that In step d), the rate of adding the second solution to the third solution is 0.1-1 mL·min -1 ; The stirring time is 1~3h, and the aging time is 4~7h.
9. A potassium-rich potassium cathode material prepared according to the method of claims 1-8.
10. A potassium ion battery comprising a positive electrode, a negative electrode, a separator and an electrolyte, characterized in that: The positive electrode is made of the potassium-rich potassium positive electrode material according to claim 9.